High‐quality diet, physical activity, and college education are associated with low risk of NAFLD among the US population - Eduardo Vilar‐Gómez; Lauren Nephew; Raj Vuppalanchi; Samer Gawrieh; Andrea Mladenovic; Francis Pike; Niharika﻿ Samala; Naga Chalasani (2021)
The effects of diet quality (DQ), physical activity (PA), and socioeconomic status (SES) on the risk of NAFLD are unclear. We examined the association among DQ, PA, SES, and NAFLD risk.